2009
DOI: 10.1189/jlb.0309214
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic alterations in chemokine gradients induce transendothelial shuttling of human T cells under physiologic shear conditions

Abstract: The active movement of cells from subendothelial compartments into the bloodstream (intravasation) has been recognized for several decades by histologic and physiologic studies, yet the molecular effectors of this process are relatively uncharacterized. For extravasation, studies based predominantly on static transwell assays support a general model, whereby transendothelial migration (TEM) occurs via chemoattraction toward increasing chemokine concentrations. However, this model of chemotaxis cannot readily r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Because E-selectin and VCAM-1 are natively expressed by bone marrow microvascular endothelium (5), we analyzed TEM of hMSCs across HUVEC monolayers stimulated to express E-selectin and VCAM-1. Our data show that HCELL + hMSCs undergo VLA-4-mediated firm adherence and TEM through stimulated HUVEC in the absence of chemokine administration; in particular, we observed heightened firm adherence of HCELL + hMSCs on HUVEC under flow conditions known to dissipate chemokine gradients (21). To specifically evaluate whether CXCR4 signaling contributes to the observed hMSC TEM, we performed PCR to measure CXCR4 mRNA levels and Western blot analysis of CXCR4 protein, to- .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Because E-selectin and VCAM-1 are natively expressed by bone marrow microvascular endothelium (5), we analyzed TEM of hMSCs across HUVEC monolayers stimulated to express E-selectin and VCAM-1. Our data show that HCELL + hMSCs undergo VLA-4-mediated firm adherence and TEM through stimulated HUVEC in the absence of chemokine administration; in particular, we observed heightened firm adherence of HCELL + hMSCs on HUVEC under flow conditions known to dissipate chemokine gradients (21). To specifically evaluate whether CXCR4 signaling contributes to the observed hMSC TEM, we performed PCR to measure CXCR4 mRNA levels and Western blot analysis of CXCR4 protein, to- .…”
Section: Discussionmentioning
confidence: 74%
“…In cases where CXCR4 expression has been reported, the chemotactic response of hMSCs to CXCL12 is modest (17). Our prior work has shown that chemokine gradients established across an endothelial interface are rapidly dissipated by hemodynamic shear forces (21), suggesting that cells bearing modest expression of chemokine receptors would be at a disadvantage in responding to perivascular chemokines in vivo. Collectively, these prior studies and our results here indicate that although chemokine(s) could cooperate in activating hMSC VLA-4 binding to endothelium and subsequent TEM in vivo, engagement of hMSC HCELL with E-selectin natively expressed on primary endothelial cells can drive this process directly.…”
Section: Discussionmentioning
confidence: 97%
“…This leukocyte reverse TEM (rTEM) response has been reported for human monocyte, neutrophil, and T cell migration through cultured endothelial cells (Buckley et al, 2006;Lee et al, 2009;Randolph and Furie, 1996) and for neutrophils in zebra fish embryos (Mathias et al, 2006). Neutrophil rTEM, and a TEM mode that involves multiple oscillatory movements within endothelial cell junctions (termed ''hesitant'' TEM), have also been observed in stimulated mouse cremasteric venules in vivo (Woodfin et al, 2011).…”
Section: Box 3 a Role For Antigenic Signals In T Cell Diapedesis Andmentioning
confidence: 81%
“…These results do not allow us to dissect the mechanism(s) behind this long lasting effect, apart from proposing resistance to cleavage hence longer presence at the inflammatory site. We cannot exclude the involvement of other pathways in the striking effect of SAnxA1, persisting within the inflamed paw, on the 24-hour edema, including promotion of retrograde leukocyte transmigration 43,44 and/or removal of apoptotic leukocytes. 9 In any case, we observed major reductions in immune cell infiltrates in the 24-hours after -carrageenan.…”
Section: Anti-inflammatory Properties Of Super Annexin A1 4293mentioning
confidence: 97%